The origins of the university: Questions of identity and historical continuity - Jaume Aurell (Church, Communication and Culture)
In this article I intend to make an inquiry into the essential values of the university in its medieval origins and to compare them with the present situation of the institution, and the main challenges it faces today. In the first part of the article, I examine the core values of the university in the twelfth and thirteenth centuries (‘Origins’). In a second section, I describe the main structural and governance features of universities in the Middle Ages, which have survived almost intact to the present day (‘Structures’). Subsequently, I detail the early difficulties the university encountered due to its first bureaucratization and formalization in the fourteenth and fifteenth centuries (‘Troubles’). Finally, I venture some conclusions on the desirability of revisiting some of the current debates surrounding the university, arguing for a return to the origins (‘Current Debates’).